Psychosocial experiences of chronic illness in individuals with an intellectual disability: A systematic review of the literature. (June 2015) - Flynn, Samantha; Hulbert-Williams, Nicholas; Hulbert-Williams, Lee; Bramwell, Ros
Background: Increased life expectancy has led to an increase in diagnoses of chronic illness in people with an intellectual disability; despite this increase, research about the psychological impact is rare. This review explored the psychosocial experiences of chronic illness in adults with an intellectual disability, revealing potential predictors and moderators of these experiences. Methods: Online databases were systematically searched to identify relevant literature, using predefined inclusion criteria. Of the 25, 058 titles initially identified, 4 were included, that is, those collecting data on people with an intellectual disability and diagnosed with cancer ( n = 2), chronic pain ( n = 1) and diabetes ( n = 1). Results: Narrative synthesis of the data identified six themes, namely, (1) delayed diagnosis, (2) information, communication and understanding, (3) negative psychological consequences, (4) negative physical consequences, (5) social perception and (6) social support. Conclusions: There are unmet needs within this population, including a lack of assistance in understanding their illness. A substantial gap in the literature should be addressed through further empirical work.